Regulation of High-Altitude Hypoxia on the Transcription of CYP450 and UGT1A1 Mediated by PXR and CAR - Duan, Ya-bin; Zhu, Jun-bo; Yang, Jian-xin; Liu, Gui-qin; Bai, Xue; Qu, Ning; Wang, Xue-jun; Li, Xiang-yang (Frontiers in Pharmacology, 2020)
Little is known about what roles the pregnane X receptor (PXR) and constitutive androstane receptor (CAR) play in drug metabolism in high-altitude hypoxia. Likewise, the potential interaction of nuclear receptors and drug metabolism enzymes during drug metabolism of high altitude hypoxia is not fully understood. In this work, we investigated the effects of high altitude hypoxia on transcriptional regulation of cytochrome P450 (CYP450) and UDP-glucuronosyltransferase 1A1 (UGT1A1) genes mediated by PXR and CAR proteins. The protein and mRNA expressions of CYP450, UGT1A1, PXR, and CAR were determined by enzyme-linked immunosorbent assay and qPCR in rats and HepG2 cell lines under hypoxia. Hypoxia potently inhibited the CYP450 isoforms, UGT1A1, PXR, and CAR protein and mRNA expression. To clarify whether PXR and CAR regulate various genes involved in drug metabolism of high altitude hypoxia, we investigated the expression of CYP1A2, CYP2C9, CYP2E1, CYP3A4, and UGT1A1 using a dual-luciferase reporter assay after treatment with Ketoconazole (KCZ) and Retinoic acid (RA), or silenced PXR and CAR gene expression. In HepG2 cells, hypoxia, KCZ, and RA inhibited CYP450 isoforms and UGT1A1 expression. Activation of PXR and CAR in cells treated with 6-(4-chlorophenyl)-imidazo (2,1-b) thiazole-5-carbaldehyde (CITCO) and rifampicin (Rif) resulted in the enhancement of CYP450 isoforms, UGT1A1, PXR, and CAR. In contrast, this effect was not observed under hypoxia. Taken together, our results suggest that hypoxia inhibits CYP1A2, CYP2C9, CYP2E1, CYP3A4, and UGT1A1 expression via the PXR and CAR regulatory pathway.